Analysis of Digital Branding Social Media Instagram Universitas Muhammadiyah Sidoarjo on Fortama 2023 Content - Elfiqi, Deliza Novian; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2024)
Nowadays, disseminating information via social media is the one of the most important aspects. Many businesses use social media to brand their brands. Social media, especially Instagram, can be used as a digital branding strategy because it allows a brand to communicate directly with consumers. By choosing the right strategy, digital branding can help companies not only to increase brand awareness, but to build good relationships with consumers. Aspects of digital branding include; visual design, brand messaging, quality content, user experience, online reputation or social interaction. There are indicators of Instagram social media including participation, openness, conversation, community and interconnectedness. The purpose of this research is to understand the aspect of digital branding and social media indicators in visual and text content uploaded on UMSIDA Instagram @umsida1912, especially on FORTAMA 2023 content. The research used a qualitative methode with a descriptive approach. Yhe analysis used is a social media analysis. The results showed that UMSIDA Instagram @umsida1912 in the FORTAMA 2023 content was able to apply digital branding aspects and social media indicators so as to create strong and positive interactions between new students.